ORGANIC PETROLOGY OF SELECTED COAL SAMPLES OF EOCENE KUARO FORMATION FROM PASIR AREA-EAST KALIMANTAN - BINARKO SANTOSO (Indonesian Mining Journal, 2011)
Eight samples of Eocene Kuaro Formation were taken from Pasir area, East Kalimantan to be examined their lithotype, maceral, mineral matter and rank of the coals in terms of geologic factors. The samples were analysed according to the ASTM (2009). The result shows the dominance of brighter lithotypes and vitrinite over liptinite, inertinite and mineral matter. There is a strong correlation between lithotype and maceral composition of the coals. The brighter lithotypes have high vitrinite content. This indicates that the coals were formed under a wet condition. The presence of high content of pyrite and calcite reflects marine incursion, in which the coals were deposited under paralic and shallow marine environment. Thus, this environment strongly supports the above correlation, where the coals were formed under the wet condition. The slight differences in the coal type can be caused by the relatively short period of peat accumulation and similarity in climate during the peat formation, and slight differences in geological setting during the Eocene period. Vitrinite reflectance (Rvmax%) values show similar ranks (mostly subbituminous A to high volatile bitumi- nous C) with a slight difference due to the thickness of cover during the coalification.